A PXY-Mediated Transcriptional Network Integrates Signaling Mechanisms to Control Vascular Development in Arabidopsis. Issue 2 (5th December 2019) - Smit, Margot E.; McGregor, Shauni R.; Sun, Heng; Gough, Catherine; Bågman, Anne-Maarit; Soyars, Cara L.; Kroon, Johannes T.; Gaudinier, Allison; Williams, Clara J.; Yang, Xiyan; Nimchuk, Zachary L.; Weijers, Dolf; et al.
Abstract : A feedforward loop that controls vascular development was uncovered by identifying a transcriptional network mediated by the receptor kinase PHLOEM INTERCALATED WITH XYLEM. Abstract: The cambium and procambium generate the majority of biomass in vascular plants. These meristems constitute a bifacial stem cell population from which xylem and phloem are specified on opposing sides by positional signals. The PHLOEM INTERCALATED WITH XYLEM (PXY) receptor kinase promotes vascular cell division and organization. However, how these functions are specified and integrated is unknown. Here, we mapped a putative PXY-mediated transcriptional regulatory network comprising 690 transcription factor-promoter interactions in Arabidopsis ( Arabidopsis thaliana ). Among these interactions was a feedforward loop containing transcription factors WUSCHEL HOMEOBOX RELATED14 (WOX14) and TARGET OF MONOPTEROS6 (TMO6), each of which regulates the expression of the gene encoding a third transcription factor, LATERAL ORGAN BOUNDARIES DOMAIN4 (LBD4). PXY signaling in turn regulates the WOX14, TMO6, and LBD4 feedforward loop to control vascular proliferation. Genetic interaction between LBD4 and PXY suggests that LBD4 marks the phloem-procambium boundary, thus defining the shape of the vascular bundle. These data collectively support a mechanism that influences the recruitment of cells into the phloem lineage, and they define the role of PXY signaling in this context in determining the arrangement of vascular tissue.